Seasonal variations of agar extracted from different life stages of Gracilaria cliftonii (Gracilariales, Rhodophyta) from Western Australia - Munoz, Julieta; Fotedar, Ravi (National Inquiry Services Centre, 2011)
Seasonality in yield, physical and chemical properties of the native agar from different life stages of Gracilaria cliftonii was investigated over a period of six seasons (autumn 2008–winter 2009). Agar yield and its properties varied as a function of seasons and life stages but there was no significant correlation between environmental factors and agar properties (p > 0.05). Native agar varied from 53.6% to 59.6% dry basis over the study period. Agar yield of the tetrasporophyte was significantly higher in autumn 2008 than spring 2009. Gelling temperature of agar varied between 34 and 36 °C, whereas melting point varied from 77 to 84.3 °C. Sulphate of the agar from different life stages of G. cliftonii varied from 5.9% to 6.6% dry basis but was not influenced by seasons (p > 0.05). The present study demonstrated that agar yield and its properties are influenced both by seasons and reproductive status of the thallus.